Explaining Psychological Statistics. - Cohen, Barry H. (Wiley, 2013)
Now in its 4th edition, this popular and comprehensive graduate-level statistics text offers students an easy to grasp and non-intimidating approach to statistics for the non-mathematician. The text provides practical coverage of SPSS in every chapter, including screen shots, procedures, exercises, and direction on how to interpret SPSS output. The use of common data sets throughout the book aid in student comprehension. Now with a new chapter showing students how to apply the right test in the right way to come out with the most accurate and true result, the new edition continues to offer students a lively and engaging introduction to the field.